Influência do tempo de doença, dose de antipsicótico e sexo sob parâmetros inflamatórios e oxidativos plasmáticos de pacientes portadores de esquizofrenia - Moreira, Roberta Tavares de Araújo (2022)
Schizophrenia is a serious, chronic and disabling mental disorder that affects the behavior of the affected individual. It is a disorder that develops by gene-environment interaction. It usually manifests itself in adolescence or early adulthood, with an average of 24 years of age, considering men and women. Regarding the influence of sex on schizophrenia, it manifests earlier with more severe symptoms in men. Neuroinflammatory and oxidative mechanisms underlie the neurobiology of schizophrenia, but these are still poorly understood. Consequently, the drugs used for its treatment are not very effective in managing some symptoms, such as cognitive ones. In view of this evidence, the aim of the present study was to evaluate the influence of disease duration, antipsychotic dose and sex on inflammatory and oxidative parameters in patients with schizophrenia (EPPs). The study was of the case-control type, with participants of both sexes without mental disorders (control group) and EPPs being recruited. The inclusion criteria for the control group were people without mental disorders, without first-degree relatives with disorders and who had not used anti-inflammatory drugs in the last 15 days prior to collection. The EPP group had to have a diagnosis of schizophrenia, be monitored by the psychiatry and endocrinology service of the Hospital Walter Cantídio UFC and not have used anti-inflammatory drugs. After collecting whole blood, the samples were centrifuged to obtain platelet-poor plasma. The levels of oxidative stress markers, such as lipid peroxidation (TBARS) and nitrite, and inflammatory response markers, such as myeloperoxidase enzyme (MPO) and Neutrophil/lymphocyte ratio (RNL) were evaluated. The results showed that, regardless of sex, there is a significant reduction in TBARS and Nitrite levels in EPPs treated with antipsychotics when compared to the healthy control group. Regarding PPEs, the clinical correlations between Chlorpromazine equivalent vs. disease duration pointed to a positive correlation, demonstrating that higher doses of antipsychotics are used by patients with longer disease duration with partial improvement of adverse effects and antioxidant defense mechanisms. A There was a correlation between the duration of illness vs. RNL, demonstrating that patients with longer disease duration have more inflammatory changes, oxidative stress products and increased levels of cytokines. The equivalent of chlorpromazine vs. TBARS showed a positive correlation with increased lipid peroxidation in female patients treated with higher doses of antipsychotics, characterizing that, over time, dose adjustment is necessary due to the patient's tolerance for the medication. In addition, the equivalent of Chlorpromazine vs. Nitrite showed a negative correlation, ie, nitrite reduction with higher doses of antipsychotics, suggesting a relationship with the chronicity of the disorder. Taken together, these data show that higher doses of antipsychotics are observed in patients with longer disease duration and are related to a reduction in blood levels of nitrite. We also observed a higher NLR in patients with longer disease duration; women, in particular, showed more lipid peroxidation when exposed to higher doses of antipsychotics.